2023
DOI: 10.1002/cssc.202201385
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Au Nanoclusters for Efficient Ammonia Electrosynthesis

Abstract: The electrochemical nitrogen (N2) reduction reaction (N2RR) under mild conditions is a promising and environmentally friendly alternative to the traditional Haber‐Bosch process with high energy consumption and greenhouse emission for the synthesis of ammonia (NH3), but high‐yielding production is rendered challenging by the strong nonpolar N≡N bond in N2 molecules, which hinders their dissociation or activation. In this study, disordered Au nanoclusters anchored on two‐dimensional ultrathin Ti3C2Tx MXene nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The last two could be further confirmed by comparing to the NMR spectra of pure sodium acetate and sodium formate compounds (Figure S1). The 1 H-1 H COSY NMR spectra in Figure 3 clearly show that 4-hydroxyvalerate and levulinate are present as products in À 175 mA/20 h. No methanol was detected in these experiments, indicating that the depolymerization does not follow the Kolbe pathways [20,21] in our catalyst system.…”
Section: Influence Of Different Currentsmentioning
confidence: 77%
“…The last two could be further confirmed by comparing to the NMR spectra of pure sodium acetate and sodium formate compounds (Figure S1). The 1 H-1 H COSY NMR spectra in Figure 3 clearly show that 4-hydroxyvalerate and levulinate are present as products in À 175 mA/20 h. No methanol was detected in these experiments, indicating that the depolymerization does not follow the Kolbe pathways [20,21] in our catalyst system.…”
Section: Influence Of Different Currentsmentioning
confidence: 77%
“…S8, † CoO/CuO-NA/CF exhibited a smaller semicircle, which further highlights good conductivity and low interfacial charge transfer resistance. [61][62][63] In addition, we conducted the electrochemical surface area (ECSA) measurements of Cu, CuO-NA/CF, and CoO/CuO-NA/CF. The obtained order of C dl for the electrodes (CoO/CuO-NA/CF (6.94 mF) > CuO-NA/CF (5.07 mF) > CF (2.54 mF)) showed that the transformation from the smooth Cu surface to the 3D morphology of the modified electrodes significantly increased the active surface area (Fig.…”
Section: Electrocatalytic No 3 Rr Performancementioning
confidence: 99%
“…structures primarily serve as active sites for SACs [ 80 ], and precisely manipulating the environmental structure surrounding metal atoms can significantly improve the electrochemical performance of catalysts [ 81 ]. In a bid to further enhance the activity of SACs, several strategies have been investigated and implemented [ 82 , 83 ]. One such strategy involves changing the coordination number of central transition metal atoms from four to five or six by adding axial coordination ligands, which alters the coordination environment and electronic structure of the central atom and allows for the regulation of electrocatalytic performance of SACs.…”
Section: Axial Coordination Design Of Sacs In Energy Electrocatalysis...mentioning
confidence: 99%